(untitled) (Research, Society and Development, 2023)
The first antibiotic was discovered in 1928 by Alexander Fleming. In Brazil, the indiscriminate use of this class of medicines leads to increasingly complex situations of bacterial resistance to antibiotics, becoming a public health problem. The objective of the study was to measure the importance of the pharmacist in the rational use of antibiotics. This is an integrative literature review, consisting of articles published between 2019 and 2021. Searches were carried out in the BVS and Google Scholar databases. The guiding question was: “How important is the role of the pharmacist in promoting the rational use of antibiotics within the hospital environment?”. In the present study, 8 articles were considered. According to Ordinance N⁰ 2,616/98, the presence of a pharmacist is guaranteed at the CCIH, in which the pharmacist plays a fundamental role in the rational use of antibiotics, however, such determinations aren’t taken into consideration by most hospitals. Studies have demonstrated the influence that skills of the pharmaceutical professional can have on the CCIH, from the storage, dispensing and standardization of medicines, in the analysis carried out on the assistance provided by the hospital pharmacist, it reports an emphasis on rational use and reduced expenses. It’s concluded that main roles of the pharmacist within the hospital environment are to promote health education, through assessment, guidance, assistance and carrying out pharmacovigilance and pharmacoeconomics. In view of this, it can be seen through this review, the constant presence of the pharmacist at the CCIH, in addition to the presence of the clinical pharmacist.